Location of the gene responsible for Rous sarcoma regression in the B-F region of the B complex (MHC) of the chicken - Plachý, J; Benda, V (Folia biologica, 1981)
We studied the fate of tumours induced by PR-RSV-C and B77-C in inbred chicken lines CB, CC and CB.R1. Rous sarcomas regressed in the CB and CB.R1 lines which are identical in the B-F region of the B complex. In contrast, progressive tumour growth was observed in the CC line which differed in the B-F region from the CB and CB.R1 lines and was identical in the B-G region with the CB.R1 line. These results suggest that the gene responsible for Rous sarcoma regression is located in the B-F region of the B complex.
Keywords: Chromosome Mapping; kur domácí; Animals; Sarcoma, Avian; zvířata; hlavní histokompatibilní komplex; spontánní regrese nádoru; ptačí sarkom; Chickens; Neoplasm Regression, Spontaneous; mapování chromozomů; Major Histocompatibility Complex